Analisis Penjualan Frozen Food Yang Paling Banyak Diminati Menggunakan Metode K-Means - Dwi Nopriyani; Hetty Rohayani; Zulfikri Akbar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Today's interest in frozen foods is very high, as frozen foods are easy to process and they can last long to store. So many households are buying frozen food for daily necessities. The purpose of this study is to know how much the purchase rate of products consumers often buy so that goods stock providers can focus more on the products that are most in demand, by using the K-Means method and by using the RapidMiner app. Where the results of the study can provide information to the business owner Frozen Food what production should be increased so that the business owner can increase the sales of Frozen Food.